Improving stormwater quality at source using catch basin inserts - Alam, M.; Anwar, Faisal; Heitz, Anna; Sarker, D. (Academic Press, 2018)
Stormwater runoff transports contaminants, including gross pollutants (GPs) accumulated on surfaces to nearby receiving water bodies. These may clog storm drainage systems, seal side entry pits and increase dissolved pollutants in receiving water bodies. Best management practices (BMPs) such as oil and grit separators, grassed swales, vegetated filter strips, retention ponds, and catch basin inserts (CBIs) are implemented to reduce stormwater pollutants in urban runoff. However, the information on physicochemical characteristics of the pollutants are still few in literature but important to improve the design of BMPs, considering qualitative aspects, and their operation. CBIs are devices used to remove GPs at source without requiring any extra land use because they are typically mounted within a catch basin (e.g. side entry pit) or existing drain. In this study, improvement of stormwater quality was investigated at two different sites (Subiaco, a residential area and Hillarys Boat Harbour, a commercial-marine-recreational area; Western Australia) where a new CBI made of non-woven polypropylene geotextile was installed in side entry pits to capture GPs at source. Influent and effluent water from the CBIs was collected and analyzed for BOD, COD, TSS and PO4-P with maximum improvements in water quality of 90%, 88%, 88% and 26% respectively. The heavy metals in influent and effluent water were found very low and below the guideline values. Analysis of particle size distribution, specific surface area of solids, SEM images and heavy metal content (Cu, Fe, Ni, Pb, Zn, Cd) in solids showed that the residential area contained more finer particles than the commercial area but that solids in the commercial area contained greater concentrations of heavy metals than those from the residential area. The specific surface area was found to be higher in the residential area and particles were thought to be largely sourced from traffic. However, these characteristics may be monitored for longer term for more CBIs installed in different locations.